Duchowe i moralne implikacje chrztu według Marka Eremity - Kamczyk, Wojciech (Collectanea Theologica, 2019)
By taking up baptismal issues in his writings, Mark the Ascetic responds to the tendencies of the Messalians, who denied the value of baptism. Pointing to the consequences of this sacrament, he emphasizes its effectiveness in terms of being freed from the consequences of Adam’s sin, as well as restoring freedom and the ability to fulfill the commandments. He highlights the priority and efficacy of grace given in a secret manner in the time of baptism. He reminds, however, that baptism does not deprive man of free will, but baptism can support it in fulfilling the Law of God. He also emphasizes the mysterious indwelling of the entire Holy Trinity in the heart of the baptized, as well as its effects. For Mark the Ascetic, baptism itself is also a “placing in the paradise of the Church”, which he understands as the ability to perform acts of love towards brethren.